Exercise and nutrition in type 1 diabetes: Insights from the FinnDiane cohort - Pongrac Barlovic, Drazenka; Harjutsalo, Valma; Groop, Per-Henrik (Frontiers in Endocrinology, 2022)
Type 1 diabetes is a challenging disease, characterized by dynamic changes in the insulin need during life periods, seasons of the year, but also by everyday situations. In particular, changes in insulin need are evident before, during and after exercise and having meals. In the midst of different life demands, it can be very burdensome to achieve tight glycemic control to prevent late diabetes complications, and at the same time, to avoid hypoglycemia. Consequently, many individuals with type 1 diabetes are faced with diabetes distress, decreasing profoundly their quality of life. Today, the nationwide Finnish Diabetic Nephropathy (FinnDiane) Study, launched in 1997, has gathered data from more than 8,000 well-characterized individuals with type 1 diabetes, recruited from 93 centers all over Finland and has established its position as the world’s leading project on studying complications in individuals with type 1 diabetes. Studying risk factors and mechanisms of diabetes complications is inconceivable without trying to understand the effects of exercise and nutrition on glycemic control and the development of diabetes complications. Therefore, in this paper we provide findings regarding food and exercise, accumulated during the 25 years of studying lives of Finnish people with type 1 diabetes.